Pengaruh Penggunaan Media Kahoot! Dalam Pembelajaran Sejarah Terhadap Minat Siswa di Kelas X SMK Negeri 1 Kotabaru Tahun Ajaran 2021/2022 - Saputra, Wahyu Setiawan; Subroto, Wisnu; Sriwati, Sriwati (Lambung Mangkurat University, 2023)
Learning at school during Covid-19 was carried out online, but caused a decrease in student interest in learning at SMK Negeri 1 Kotabaru. As for teacher complaints, such as the lack of facilities and infrastructure using more interactive learning media, such as Kahoot!, because teachers tend to use simple learning media, such as Power Point. Even though learning media is a means that can be used as an intermediary in the learning process to increase effectiveness and efficiency in achieving learning objectives. This study aims to determine the effect of using Kahoot! towards students' learning interest in history learning at SMK Negeri 1 Kotabaru. This study used Quasi Experimental Design with Nonequivalent Control Group Design. The population used is class X, with purposive sampling techniques, then the research sample is class X RPL as the experimental class and class X AKL 2 as the control class. Data collection techniques using questionnaires and documentation. Trials of research instruments are carried out with validity and reliability. Testing data analysis techniques, namely with prerequisites, homogeneity and hypotheses. The results of calculations through t-tests, data on learning interest in the experimental class averaged 118.1818, while learning interest in the control class averaged 80.2333. From these data, the Independent Samples Test shows the sig value. 0.00 < 0.05 so Ho rejected Ha accepted. In conclusion, after t-test treatment with Independent Samples Test there was a significant effect on using Kahoot! towards the learning interest of grade X students at SMK Negeri 1 Kotabaru.